2009
DOI: 10.1124/mol.109.061051
|View full text |Cite
|
Sign up to set email alerts
|

Crofelemer, an Antisecretory Antidiarrheal Proanthocyanidin Oligomer Extracted from Croton lechleri, Targets Two Distinct Intestinal Chloride Channels

Abstract: Crofelemer, a purified proanthocyanidin oligomer extracted from the bark latex of Croton lechleri, is in clinical trials for secretory diarrheas of various etiologies. We investigated the antisecretory mechanism of crofelemer by determining its effect on the major apical membrane transport and signaling processes involved in intestinal fluid transport. Using cell lines and measurement procedures to isolate the effects on individual membrane transport proteins, crofelemer at 50 M had little or no effect on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
111
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(117 citation statements)
references
References 35 publications
6
111
0
Order By: Relevance
“…Our data and the above reports 22,23) suggest that proanthocyanidin inhibits 5-HT 3 receptors in a noncompetitive manner, and that there exits the possibility that proanthocyanidin acts as an open channel blocker at 5-HT 3 receptors. Therefore, we tested the voltage dependency of the inhibition by proanthocyanidin by measuring its effect on current-voltage relationships.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Our data and the above reports 22,23) suggest that proanthocyanidin inhibits 5-HT 3 receptors in a noncompetitive manner, and that there exits the possibility that proanthocyanidin acts as an open channel blocker at 5-HT 3 receptors. Therefore, we tested the voltage dependency of the inhibition by proanthocyanidin by measuring its effect on current-voltage relationships.…”
Section: Discussionmentioning
confidence: 48%
“…Prior studies suggested that proanthocyanidin is membrane-impermeable because of its size and polarity and that it seems unlikely that it is transported across the membrane at a sufficient rate to reach a potential intracellular target. 22,23) Thus, the noncompetitive inhibition of 5-HT 3 receptor channel activity by proanthocyanidin indicates that proanthocyanidin has different binding or interaction sites through which it modulates the 5-HT 3 ion channel from the extracellular side.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the antisecretory properties of crofelemer are based on a dual mechanism of action. 15 Finally, the chloride channel type-2 channels are located on the lateral membranes of enterocytes, and their role in chloride-ion secretion is not well understood.…”
Section: Mechanisms Associated With Secretory Diarrheamentioning
confidence: 99%
“…The two chloride channels are cAMPstimulated cystic fibrosis transmembrane conductance regulator (CFTR) and CaCC. 15 Inhibition of chloride-ion secretion results in decreased efflux of sodium and water and, therefore, improvement in diarrheal symptoms. 15 In the study performed by Tradtrantip et al, 15 crofelemer demonstrated a concentration-dependent inhibition on both the luminal CFTR channels, as well as an even stronger inhibition of the CACCs.…”
Section: Pharmacodynamicsmentioning
confidence: 99%
See 1 more Smart Citation